Treatment of chronic urticaria with omalizumab: the experience of Hospital de Braga - Ana G. Lopes; Marianlie Navarro; Carmem Botelho; Maria J. Guimarães; Catarina Cerqueira; Joana Gomes; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Introduction: Omalizumab is approved for the treatment of severe chronic spontaneous urticaria (CSU), unresponsive to quadruple doses of nonsedative H1 antihistamine. Few data are available to help predict the response to omalizumab in the Portuguese population. Objective: Characterize the population of CU patients treated with omalizumab in Hospital de Braga and identify variables that help predict a better response to omalizumab. Methods: Retrospective chart-review study of CU patients treated with omalizumab in Hospital de Braga. Statistical analysis was performed using the chi-square, odds ratio analysis and generalized linear models. Results: 21 patients were included (three men and 18 women). 16 patients had CSU, two had solar urticaria, two cholinergic urticaria, and one cold urticaria. They all had at least 6 months of treatment with omalizumab. Prior to omalizumab, they all had been treated with quadruple doses of nonsedating H1 antihistamines. Using generalized linear models, patients showed a significant reduction of the UAS and UAS7 scores. Women and patients with intermediate levels of immunoglobulin (Ig)-IgE presented a bigger reduction. Women had higher total serum IgE. Conclusion: The female gender and patients with intermediate levels of IgE had a better response to omalizumab. In this study, the female gender seems to have higher total serum IgE.